2015
DOI: 10.1136/medhum-2015-010704
|View full text |Cite
|
Sign up to set email alerts
|

Shared Reading: assessing the intrinsic value of a literature-based health intervention

Abstract: Public health strategies have placed increasing emphasis on psychosocial and arts-based strategies for promoting well-being. This study presents preliminary findings for a specific literary-based intervention, Shared Reading, which provides community-based spaces in which individuals can relate with both literature and one another. A 12-week crossover design was conducted with 16 participants to compare benefits associated with six sessions of Shared Reading versus a comparison social activity, Built Environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 23 publications
3
48
1
Order By: Relevance
“…Nobody knows why this text resonates personally for T, not even the facilitator. This is what we might call implicit therapy,31 doing its own work hiddenly in the moment of reading. Perhaps a very great deal of what happens in SR must remain thus hidden from view.…”
Section: Results and Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nobody knows why this text resonates personally for T, not even the facilitator. This is what we might call implicit therapy,31 doing its own work hiddenly in the moment of reading. Perhaps a very great deal of what happens in SR must remain thus hidden from view.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Together with qualitative findings that reading ‘stimulates metacognition and high-level mentalisation in relation to deepened and expanded emotional investment in human pursuits (created by the book)’,31 it is possible, a recent neurological study has suggested, that some of the benefit associated with reading may come from ‘diverting individuals away from processing their struggles via ingrained and ineffective channels and towards more diverse, novel and effective reasoning options’ 34. These findings seem particularly relevant to a condition in which the nervous system is ‘recruiting’ signals into an existing pain pathway and sending messages to the brain when there is no physical stimulus or damage 35.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The assumption that taste needs to be ‘elevated’ to guide the reader on a path to self-improvement can be seen throughout the history of reading 16. In modern schemes aimed at engaging people with literature, a distinction is often made between the classics and other fiction 20. Reading certain books (including the classics) is still associated with symbolic mastery and increased cultural capital 7…”
Section: Introductionmentioning
confidence: 99%